The Impact of Framing on Acceptance of Cultured Meat - Bryant, Christopher; Dillard, Courtney (Frontiers in Nutrition, 2019)
Cultured meat can be produced from growing animal cells in-vitro rather than as part of a living animal. This technology has the potential to address several of the major ethical, environmental, and public health concerns associated with conventional meat production. However, research has highlighted some consumer uncertainty regarding the concept. Although several studies have examined the media coverage of this new food technology, research linking different frames to differences in consumer attitudes is lacking. In an experimental study, we expose U.S. adults (n = 480) to one of three different frames on cultured meat: ‘societal benefits’, ‘high tech’, and ‘same meat’. We demonstrate that those who encounter cultured meat through the ‘high tech’ frame have significantly more negative attitudes towards the concept, and are significantly less likely to consume it. Worryingly, this has been a very dominant frame in early media coverage of cultured meat. Whilst this is arguably inevitable, since its technologically advanced nature is what makes it newsworthy, we argue that this high tech framing may be causing consumers to develop more negative attitudes towards cultured meat than they otherwise might. Implications for producers and researchers are discussed.